Experimental Testing of Bionic Peripheral Nerve and Muscle Interfaces: Animal Model Considerations - Aman, Martin; Bergmeister, Konstantin D.; Festin, Christopher; Sporer, Matthias E.; Russold, Michael Friedrich; Gstoettner, Clemens; Podesser, Bruno K.; Gail, Alexander; Farina, Dario; Cederna, Paul; Aszmann, Oskar C. (Frontiers in Neuroscience, 2020)
Introduction: Man-machine interfacing remains the main challenge for accurate and reliable control of bionic prostheses. Implantable electrodes in nerves and muscles may overcome some of the limitations by significantly increasing the interface’s reliability and bandwidth. Before human application, experimental preclinical testing is essential to assess chronic in-vivo biocompatibility and functionality. Here we analyze available animal models, their costs and ethical challenges in special regards to simulating a potentially life-long application in a short period of time and in non-biped animals. Methods: We performed a literature analysis following the PRISMA guidelines including all animal models used to record neuromuscular activity via implantable electrodes, evaluating animal models, group size, duration, origin of publication as well as type of interface. Furthermore, behavioral, ethical and economic considerations of these models were analyzed. Additionally, we discuss experience and surgical approaches with rat, sheep, and primate models and an algorithm for international standardized testing. Results: Overall, 343 studies matched the search terms, dominantly originating from the US (55%) and Europe (34%), using mainly small animal models (rat: 40%). Electrode placement was dominantly neural (77%) compared to muscular (23%). Large animal models had a mean duration of 135  87.2 days, with a mean of 5.3  3.4 animals per trial. Small animal models had a mean duration of 85  11.2 days, with a mean of 12.4  1.7 animals. Discussion: Only 37% animal models were by definition chronic tests (>3 months) and thus potentially provide information on long-term performance. Costs for large animals were up to 45 times higher than small animals. However, costs are comparably small compared to complication costs in human long-term applications. Overall, we believe a combination of small animals for preliminary primary electrode testing and large animals to investigate long-term biocompatibility, impedance, and tissue regeneration parameters provides sufficient data to ensure long-term human applications